Evaluation of polymer flooding in multi-layered heterogeneous reservoir: the study of viscosity and injection rate of polymer solution - Aniwan Panthangkool (Chulalongkorn University, 2014)
Thesis (M.Eng.)--Chulalongkorn University, 2012